2005
DOI: 10.1523/jneurosci.3801-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Influences Cocaine-Induced Blood Oxygen Level-Dependent Signal Changes in Female Rats

Abstract: We investigated the effect of estrogen on cocaine-induced brain activity using blood oxygen level-dependent (BOLD) magnetic resonance imaging. Ovariectomized (Ovx) rats without estrogen and Ovx rats with estrogen (OvxϩE) were given a single saline or cocaine injection (15 mg/kg, i.p.) for 5 d. After 7 d of withdrawal from injections, rats were challenged with cocaine during functional imaging. Acute cocaine administration produced positive BOLD activation in the prefrontal cortex, nucleus accumbens, striatum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 49 publications
3
30
1
Order By: Relevance
“…Implants were air dried and incubated in sterile saline for at least 12e16 hours to allow the initial surge of high-estradiol levels to be released before use. It has been observed that such implants achieve stable levels of plasma estradiol over 30 days, with a release rate of 75e100 pg/mL per 24 hours (see Febo et al, 2005), as confirmed in our previous studies (Rodriguez-Perez et al, 2010. However, stable levels of E2 have also been found to persist for only 7e24 days (Mannino et al, 2005).…”
Section: Estrogen and Candesartan Administration And Intrastriatal Insupporting
confidence: 81%
See 2 more Smart Citations
“…Implants were air dried and incubated in sterile saline for at least 12e16 hours to allow the initial surge of high-estradiol levels to be released before use. It has been observed that such implants achieve stable levels of plasma estradiol over 30 days, with a release rate of 75e100 pg/mL per 24 hours (see Febo et al, 2005), as confirmed in our previous studies (Rodriguez-Perez et al, 2010. However, stable levels of E2 have also been found to persist for only 7e24 days (Mannino et al, 2005).…”
Section: Estrogen and Candesartan Administration And Intrastriatal Insupporting
confidence: 81%
“…Rats were bilaterally ovariectomized through a dorsal incision and simultaneously (group B) or 6 weeks (group C) or 20 weeks (group D) later received Silastic implants (inserted subcutaneously) in the midscapular region (Dziuk and Cook, 1966;Febo et al, 2005). Silastic implants were prepared with Silastic tubing (1.47 mm inner diameter  1.95 mm outer diameter, Dow Corning 508-006; VWR Scientific, Bridgeport, NJ), as described by Febo et al (2005).…”
Section: Estrogen and Candesartan Administration And Intrastriatal Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data with fMRI demonstrate that estradioltreated female rats sensitized to cocaine show enhanced BOLD activity in brain areas of the reward pathway (Febo et al, 2005), suggesting that estradiol alters the activity of neurotransmitter and/or neuropeptide systems of the reward pathway, which may enhance the behavioral response to cocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Functional imaging of the brain in awake rodents has proven its utility since its inception nearly two decades ago (Lahti et al, 1998), and has elevated our understanding in a variety of scientific disciplines, including absence seizures (Tenney et al, 2004), maternal care (Febo and Ferris, 2007; Ferris et al, 2005), pain (Yee et al, 2015), reward (Kulkarni et al, 2012), neurodegenerative diseases (Ferris et al, 2014), and drugs of abuse (Febo et al, 2005, 2004; Febo and Ferris, 2007; Madularu et al, 2015). The utility of functional imaging in rodents is largely translational.…”
Section: Introductionmentioning
confidence: 99%